Gamma irradiation induced Sn-based brazing filler metal surface nanocrystalline oxide layer and preparation method thereof
Through gamma irradiation technology, a uniform nanocrystalline oxide layer is formed on the surface of Sn-based brazing at room temperature and pressure, which solves the problem of slow and uneven growth of the oxide layer on the surface of Sn-based brazing, and improves corrosion resistance and production efficiency. The process is environmentally friendly and cost-reduced.
Patent Information
- Application Number
- CN202411290336.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-14
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2044-09-14
AI Technical Summary
During use, the surface oxide layer of the existing Sn-based solder is slow and uneven, which affects its corrosion resistance. The existing modification methods are costly and are prone to introduce impurities, and lack systematic research methods and process parameter optimization.
The Sn-based brazing material was treated under normal temperature and pressure conditions by using gamma irradiation technology. The γ ray emitted by 60Co source is induced to form a uniform nanocrystalline oxide layer on the surface of the Sn-based brazing material. The surface pretreatment and optimization of process parameters are carried out by the surface pretreatment and optimization of process parameters such as The radiation dose rate and time were used to form a nanocrystalline oxide layer with an average grain diameter of 10-20 nm and an oxide layer thickness of 50-1 μm.
It significantly shortens the oxide growth cycle, improves the upper limit of oxide thickness and corrosion resistance, improves the corrosion resistance and production efficiency of solder, and has a friendly process and low cost.
Smart Images

Figure CN119216874A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to radiation-induced solder nanocrystal oxidation and a preparation method thereof, belonging to the technical field of nano material preparation. Background Art
[0002] With the development of the electronics industry and materials science, solder plays an important role in electronic packaging and connection technology. Sn-based solder is widely used in the interconnection of electronic devices due to its excellent wettability, low melting point and good mechanical properties. However, with the miniaturization and high performance of integrated circuits and electronic devices, higher requirements are placed on the performance of solder, especially the increasing demand for its corrosion resistance and mechanical stability.
[0003] In the prior art, Sn-based solders tend to form an oxide layer on their surface during use. Although this phenomenon can prevent further oxidation to a certain extent, the traditional oxide layer grows slowly and unevenly, affecting the overall performance of the solder. In order to improve the corrosion resistance of the solder surface, researchers have tried to modify it through a variety of methods, such as electroplating, chemical vapor deposition, and physical vapor deposition. However, these methods usually require complex equipment and processes, are costly, and are prone to introducing impurities during the processing process, affecting the purity and performance of the final product.
[0004] As an emerging material modification method, γ-irradiation technology has the advantages of uniform treatment, strong penetration, and environmental friendliness, and has shown broad application prospects in the field of material modification. γ-ray irradiation can effectively induce physical and chemical changes on the surface of materials under normal temperature and pressure conditions, generating a uniform and dense nanocrystalline oxide layer, thereby improving the corrosion resistance of the material. However, the current research on γ-irradiation modification of Sn-based solders is still in its infancy, lacking systematic research methods and optimization of process parameters.
[0005] Therefore, it is urgent to propose a γ-irradiation-induced Sn-based solder surface nanocrystalline oxide layer and a preparation method thereof to solve the above technical problems. Summary of the invention
[0006] In order to solve the above problems, a γ-irradiation-induced nanocrystalline oxide layer on the surface of Sn-based solder and a preparation method thereof are provided. A brief overview of the invention is given below to provide a basic understanding of certain aspects of the invention. It should be understood that this overview is not an exhaustive overview of the invention. It is not intended to determine the key or important parts of the invention, nor is it intended to limit the scope of the invention.
[0007] The technical solution of the present invention:
[0008] A gamma irradiation-induced Sn-based solder surface nanocrystalline oxide layer is prepared by a gamma irradiation-induced Sn-based solder surface nanocrystalline oxidation preparation method. The average grain diameter of the Sn-based solder surface oxide nanocrystals in the Sn-based solder surface nanocrystalline oxide layer is 10-20nm, and the oxide layer thickness is 50nm-1μm.
[0009] A method for preparing Sn-based solder surface nanocrystals by gamma irradiation-induced oxidation, comprising the following steps:
[0010] Step 1: Surface pretreatment of the solder;
[0011] Step 2: Electron irradiation of the solder.
[0012] Preferably: in step 1, the solder surface is sanded and polished and then dried to remove surface impurities, the sandpaper polishing is 80 mesh, 240 mesh, 800 mesh, 1500 mesh, 2000 mesh and 3000 mesh in sequence, and the polishing is carried out using 0.5 μm diamond polishing agent and water polishing in sequence.
[0013] Preferably: Step 2 comprises the following steps:
[0014] Step 2.1: The Sn-based solder sample is placed in a γ irradiation device, in which a potassium silver dichromate dose meter is provided, and the γ irradiation dose rate in the irradiation room is measured;
[0015] Step 2.2: Use 60 The solder samples were gamma-irradiated by gamma rays emitted by Co source;
[0016] Step 2.3: Obtain a solder having a nanocrystalline oxide layer on the surface.
[0017] Preferably: in step 2.1, the solder sample is fixed on the platform surface.
[0018] Preferably, in step 2.2, the irradiation dose rate is 0.05 gy (Si) / s to 0.5 gy (Si) / s, the irradiation time is 300 h to 5000 h, and the total irradiation dose is 5.4 × 10 4 gy~9×10 6 gy.
[0019] Preferably: a method for preparing a nanocrystalline oxide layer on the surface of a Sn-based solder induced by γ-irradiation is applied to oxidation of the Sn-based solder.
[0020] Preferably: the Sn-based solder (solder) includes Sn a1 Bi b1 and / or Sn a1 Zn b1Alloy, wherein a1 and a2 correspond to the mass percentage content of atoms of each element, 50%≤a1≤100%, 5,0%≤b1≤50%, a1+b1=100%.
[0021] Preferably, the diameter of the platform is 10 cm, in step 2.2, the temperature is 40° C. to 70° C., and the platform rotation speed is 10 rpm to 60 rpm.
[0022] Preferably, the Sn-based solder is in the form of flakes, filaments, spheres, blocks, powders, columns, foils or pastes, or a combination of these.
[0023] The present invention has the following beneficial effects:
[0024] The present invention provides a method for preparing a nanocrystalline oxide layer on the surface of a Sn-based solder induced by γ irradiation. 60 By irradiating the surface of Sn-based solder with Co source gamma rays, uniform nanocrystalline oxide grains can be obtained on the solder surface, and the growth cycle of oxides on the solder surface can be greatly shortened, the upper limit of oxide thickness can be increased, and the corrosion resistance of the material can be improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 For not passed 60 Low and high magnification SEM images of SnBi eutectic solder joints irradiated by Co source γ-rays at room temperature and pressure for 2000 hours;
[0026] Figure 2 After 200h, the dose rate is 0.1gy(Si) / s 60 Low and high magnification SEM images of SnBi eutectic solder joints after Co source γ-ray irradiation;
[0027] Figure 3 For not passed 60 Co source γ-ray irradiation of SnBi eutectic solder balls placed at room temperature and pressure for 2000 hours and irradiated for 200 hours with a dose rate of 0.1gy(Si) / s 60 Shear force-displacement curve of SnBi eutectic solder ball after Co source γ-ray irradiation;
[0028] Figure 4 For the unirradiated and 1000h irradiated conditions, the dose rate is 0.3gy(Si) / s 60 TEM bright field image and HRTEM image of SnZn eutectic solder joint after Co source γ-ray irradiation;
[0029] Figure 5 For not passed 60Co source γ-ray irradiation of SnZn eutectic solder balls placed at room temperature and pressure for 2000 hours and irradiated for 1000 hours, with a dose rate of 0.3gy(Si) / s 60 Shear force-displacement curve of SnZn eutectic solder ball after Co source γ-ray irradiation;
[0030] Figure 6 For the unirradiated and 1000h irradiated, 0.2gy(Si) / s dose rate 60 TEM bright field image and HRTEM image of Sn96.5Ag3Cu0.5 solder joint after Co source γ-ray irradiation;
[0031] Figure 7 Schematic diagram of the irradiation device structure.
[0032] In the figure: 1- connecting rod structure, 2- irradiation chamber shell, 3- irradiation source, 4- platform, 5- one-way valve, 6- bottom plate, 7- solder. DETAILED DESCRIPTION
[0033] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is described below by the specific embodiments shown in the accompanying drawings. However, it should be understood that these descriptions are only exemplary and are not intended to limit the scope of the present invention. In addition, in the following description, the description of well-known structures and technologies is omitted to avoid unnecessary confusion of the concept of the present invention.
[0034] Specific implementation method 1: Combination Figure 1-6 The present embodiment is described. A γ-irradiation-induced Sn-based solder surface nanocrystalline oxide layer is prepared by a γ-irradiation-induced Sn-based solder surface nanocrystalline oxidation preparation method. The Sn-based solder surface nanocrystalline oxide layer has an average grain diameter of 10-20nm and an oxide layer thickness of 50nm-1μm. The present invention solves the problems of slow growth, uneven oxide grain size and thin oxide layer thickness of the naturally generated Sn-based solder surface oxide layer under existing room temperature conditions. The corrosion resistance and production efficiency of the Sn-based solder surface nanocrystalline oxide layer are improved by optimizing the process method and process parameters.
[0035] Specific implementation method 2: Combination Figure 1-7 This embodiment is described. A method for preparing Sn-based solder surface nanocrystals by gamma irradiation-induced oxidation in this embodiment includes the following steps:
[0036] Step 1: Surface pretreatment of the solder;
[0037] Step 2: Electron irradiating the solder;
[0038] The present invention proposes a method for preparing a nanocrystalline oxide layer on the surface of a Sn-based solder induced by γ-irradiation, by using a 60 The gamma rays emitted by the Co source are used to irradiate the Sn-based solder, forming uniform nanocrystalline oxide grains on the surface of the solder. This method can not only significantly shorten the oxide growth cycle, increase the upper limit of oxide thickness, and the oxidation quality of the deep oxide layer, but also significantly improve the corrosion resistance of the Sn-based solder, which has important application value and broad market prospects.
[0039] Specific implementation method three: Combination Figure 1-7 The present embodiment is described. The present embodiment is a method for preparing Sn-based solder surface nanocrystals by γ-irradiation-induced oxidation. In step 1, a suitable Sn-based solder sample is selected, and its surface is pre-treated by grinding and polishing and then placed in a vacuum drying oven to remove surface impurities and oxide layers. The sandpaper grinding is 80 mesh, 240 mesh, 800 mesh, 1500 mesh, 2000 mesh and 3000 mesh, respectively. The polishing uses 0.5 μm diamond polishing agent and water polishing, respectively.
[0040] Specific implementation method four: Combination Figure 1-7 This embodiment is described. In this embodiment, a method for preparing Sn-based solder surface nanocrystals by γ-irradiation-induced oxidation is described. Step 2 includes the following steps:
[0041] Step 2.1: Place the potassium silver dichromate dosing agent into 60 In the Co source γ irradiation device room, the sample needs to be fixed when rotating, and can be fixed or not fixed under lifting conditions to measure the γ irradiation dose rate;
[0042] Step 2.2: Use 60 The gamma rays emitted by the Co source are used to gamma-irradiate the solder samples. As an emerging material modification method, gamma irradiation technology has the advantages of uniform treatment, strong penetration, and environmental friendliness, and has shown broad application prospects in the field of material modification. Gamma ray irradiation can effectively induce physical and chemical changes on the surface of the material under normal temperature and pressure conditions, generating a uniform and dense nanocrystalline oxide layer, thereby greatly improving the corrosion resistance of the material. However, the research on gamma irradiation modification of Sn-based solder is still in its infancy, lacking a systematic research method and optimization of process parameters.
[0043] Step 2.3: Obtain a solder with a nanocrystalline oxide layer on the surface; this can be used under normal temperature and pressure conditions. 60 By irradiating Sn-based solder with gamma rays emitted by a Co source, uniform nanocrystalline oxide grains can be obtained on the solder surface, and the growth cycle of oxides on the solder surface can be greatly shortened, and the upper limit of oxide thickness can be increased; the corrosion resistance of Sn-based solder can be greatly improved.
[0044] Specific implementation method five: Combination Figure 1-7 The present embodiment is described. The present embodiment is a method for preparing Sn-based solder surface nanocrystals by γ irradiation-induced oxidation. In step 2.1, the solder sample is fixed on the surface of the platform, and the fixed sample and the rotating heating platform are placed in a γ irradiation device. The irradiation device used includes an irradiation chamber housing 2, a radiation source 3 ( 60 Co-γ irradiation source), platform 4, two one-way valves 5 and bottom plate 6. The top of the irradiation chamber shell 2 is provided with a irradiation source 3, the inlet and outlet pipes on the left and right sides of the upper part of the irradiation chamber shell 2 are provided with one-way valves 5, the side wall of the irradiation chamber shell 2 is provided with an openable and closable door for taking and placing the solder 7, the platform 4 is arranged in the room of the irradiation chamber shell 2, the platform 4 is used to place the solder 7, the platform 4 is provided with a heating device for adjusting the temperature of the sample to improve the efficiency, the irradiation chamber shell 2 is fixedly provided on the bottom plate 6, the bottom plate 6 is connected to the platform 4 for rotation or lifting; a chassis is placed on the bottom plate 6, a motor is connected with bolts on the top of the chassis, the output end of the motor is connected to the rotating shaft through a gearbox, and the rotating shaft is connected to the middle of the platform 4 with a key connection, so that the platform can be stably placed in the irradiation room, the experimental condition is normal pressure air condition, the irradiation source is started, and the platform is rotated, driving the sample on the horizontal platform to rotate; when the bottom plate 6 is connected to the platform 4 for lifting, the irradiation device also includes a connecting rod structure 1, the connecting rod structure 1 is more than two groups, and the connecting rod structure 1 includes two hinged connecting rods. The two ends of the connecting rod structure 1 are hinged with the platform 4 and the bottom plate 6 respectively. The edge of the platform 4 is slidably connected with the inner wall of the irradiation chamber shell 2 through a sealed linear bearing. The inner wall of the irradiation chamber shell 2 is provided with a stopper to limit the lowest point position of the platform 4. The lower space of the platform 4 is connected with the atmosphere. After the brazing material is placed and the irradiation chamber shell door and valve are closed, the brazing material is placed in the closed irradiation chamber, the inlet one-way valve is opened to introduce oxygen, and the irradiation chamber is purged. The purged gas is discharged through the outlet one-way valve, so that the irradiation chamber is filled with oxygen. After the gas is filled, the inlet one-way valve is closed, and the gas is pumped through the outlet pipe to adjust the distance between the platform and the irradiation source to adjust the vertical position of the solder. After the adjustment is completed, the irradiation source is started. During the process of oxygen consumption by the solder, the gas in the irradiation chamber on the upper side of the platform decreases and the pressure decreases. Without consuming additional energy, the platform 4 rises as the oxygen is consumed, so that the solder is irradiated evenly in the vertical direction. At the same time, as the space decreases, the unit oxygen content remains basically the same, which is suitable for deep oxidation, not only improving the irradiation efficiency, but also improving the irradiation quality.
[0045] Specific implementation method six: Combination Figure 1-7 The present embodiment is described as a method for preparing Sn-based solder surface nanocrystals by γ-irradiation-induced oxidation. In step 2.2, the irradiation dose rate is 0.05gy(Si) / s to 0.5gy(Si) / s, and the irradiation time is any combination of dose rate and irradiation time in the range of 300h to 5000h to irradiate the Sn-based solder sample.
[0046] Specific implementation method seven: Combination Figure 1-7 The present embodiment is described. A method for preparing nanocrystalline oxidation on the surface of Sn-based solder induced by γ irradiation and a method for preparing nanocrystalline oxide layer on the surface of Sn-based solder induced by γ irradiation are applied to the oxidation of Sn-based solder.
[0047] Specific implementation method eight: Combination Figure 1-7 The present embodiment is described as follows: a method for preparing Sn-based solder surface nanocrystals by γ-irradiation-induced oxidation, wherein the Sn-based solder comprises Sn a1 Bi b1 and / or Sn a1 Zn b1 Alloy, wherein a1 and a2 correspond to the mass percentage content of atoms of each element, 50%≤a1≤100%, 5,0%≤b1≤50%, a1+b1=100%.
[0048] Specific implementation method nine: Combination Figure 1-7 The present embodiment is described. The present embodiment is a method for preparing nanocrystalline oxidation on the surface of Sn-based solder by γ-irradiation-induced oxidation. The platform diameter is 10 cm. In step 2.2, during the irradiation process, the irradiation chamber temperature is 40°C to 70°C, and the platform rotation speed is 10rpm to 60rpm, thereby achieving controllable preparation of nanocrystalline oxide layer on the surface of Sn-based solder with an average grain diameter of 10-20nm and an oxide layer thickness of 50nm-1μm.
[0049] Specific implementation method ten: Combination Figure 1-7 The present embodiment is described as a method for preparing surface nanocrystals of Sn-based solder by γ-irradiation-induced oxidation. The Sn-based solder is in the form of one or more of flakes, filaments, spheres, blocks, powders, columns, foils or pastes.
[0050] Embodiment 1:
[0051] A method for preparing a nanocrystalline oxide layer on the surface of a Sn-based solder induced by γ-irradiation, comprising the following steps:
[0052] S1. The SnBi eutectic solder ball with a diameter of 400 μm is polished with 80 mesh, 240 mesh, 800 mesh, 1500 mesh, 2000 mesh and 3000 mesh sandpaper in sequence, and then polished with 0.5 μm diamond polishing agent and water polished, and the polished solder joint is placed in a vacuum drying oven;
[0053] S2. Place the potassium silver dichromate dosage agent into 60 In the Co source gamma irradiation device room (irradiation room), mark the position where the irradiation dose rate is 0.2gy(Si) / s;
[0054] The pretreated SnBi eutectic solder ball sample was placed on the surface of the rotating heating platform (platform 2), and the temperature of the rotating heating platform was selected to be 50°C and the rotation speed was 60rpm;
[0055] The polished SnBi eutectic alloy solder ball was irradiated with a dose rate of 0.1gy(Si) / s for 200h. 60 Co source γ irradiation.
[0056] See also Figure 1 As shown, it is not 60 Low-magnification and high-magnification SEM images of the surface of the SnBi eutectic solder joint that was irradiated by Co source γ and placed in a room temperature and pressure environment for 200 hours; it can be found that the solder joint surface is smooth and no oxide is generated. Figure 2 As shown, the irradiation time is 200h at a dose rate of 0.1gy(Si) / s under normal temperature and pressure. 60 Low-magnification and high-magnification SEM images of the surface of the SnBi eutectic solder joint after Co source γ-irradiation; it can be found that a dense Sn oxide layer has grown on the surface of the solder joint; see Figure 3 As shown in Figure 1, Figure (a) is the force-displacement curve of the solder ball without γ irradiation, and Figure (b) is the force-displacement curve of the solder ball after irradiation for 200 hours and a dose rate of 0.1gy(Si) / s. 60 Force-displacement curve of SnBi eutectic solder ball after Co source γ irradiation. After irradiation time of 200h and dose rate of 0.1gy(Si) / s 60 The shear force of the SnBi eutectic solder ball after Co source γ irradiation increased from 544.17g to 589.88g, and the shear force increased by 8.40%.
[0057] Embodiment 2:
[0058] A method for preparing a nanocrystalline oxide layer on the surface of a Sn-based solder induced by γ-irradiation, comprising the following steps:
[0059] S1. The SnZn eutectic solder ball with a diameter of 400 μm was polished with 80 mesh, 240 mesh, 800 mesh, 1500 mesh, 2000 mesh and 3000 mesh sandpaper in sequence, and then polished with 0.5 μm diamond polishing agent and water polished, and the polished solder joint was placed in a vacuum drying oven;
[0060] S2. Place the potassium silver dichromate dosage agent into 60 In the Co source gamma irradiation device room, mark the position where the irradiation dose rate is 0.2gy(Si) / s;
[0061] The pretreated SnZn eutectic solder ball sample was placed on the surface of the rotating heating platform, and the temperature of the rotating heating platform was selected to be 50°C and the rotation speed was 60rpm;
[0062] The polished SnZn eutectic solder ball was subjected to a dose rate of 0.3gy(Si) / s for 1000h. 60 Co source gamma irradiation; see Figure 5 As shown, Figure (a) is a bright field phase image of the SnZn eutectic TEM sample without γ irradiation; it can be found that there is no oxide in the Sn crystal; Figure (b) is a bright field phase image of the SnZn eutectic TEM sample after irradiation at a dose rate of 0.3gy(Si) / s for 1000h; it can be found that a large number of Sn oxide nanocrystals appear in the Sn crystal; Figure (c) is a HRTEM image of the SnZn eutectic TEM sample after irradiation at a dose rate of 0.3gy(Si) / s for 1000h; it can be found that a large number of SnO2 nanocrystals corresponding to the SnO2 lattice structure appear in the Sn crystal; see Figure 6 As shown in Figure 1, Figure (a) is the force-displacement curve of the solder ball without γ irradiation, and Figure (b) is the force-displacement curve of the solder ball after irradiation for 1000h and a dose rate of 0.3gy(Si) / s. 60 Force-displacement curve of SnZn eutectic solder ball after Co source γ irradiation. After irradiation time of 1000h and dose rate of 0.3gy(Si) / s 60 The shear force of the SnZn eutectic solder ball after Co source γ irradiation increased from 488.68g to 563.95g, and the shear force increased by 15.40%.
[0063] Embodiment 3:
[0064] A method for preparing a nanocrystalline oxide layer on the surface of a Sn-based solder induced by γ-irradiation, comprising the following steps:
[0065] S1. A Sn96.5Ag3Cu0.5 solder ball with a diameter of 400 μm is polished with 80 mesh, 240 mesh, 800 mesh, 1500 mesh, 2000 mesh and 3000 mesh sandpaper in sequence, and then polished with 0.5 μm diamond polishing agent and water polished, and the polished solder joint is placed in a vacuum drying oven;
[0066] S2. Place the potassium silver dichromate dosage agent into 60 In the Co source gamma irradiation device room, mark the position where the irradiation dose rate is 0.2gy(Si) / s;
[0067] The polished Sn96.5Ag3Cu0.5 solder ball was subjected to a dose rate of 0.2gy(Si) / s for 250h. 60 Co source gamma irradiation. Figure 6As shown, Figure (a) is the bright field phase image of the Sn96.5Ag3Cu0.5 TEM sample without γ irradiation; it can be found that there is no oxide in the Sn crystal; Figure (b) is the bright field phase image of the Sn96.5Ag3Cu0.5 TEM sample after irradiation at a dose rate of 1gy(Si) / s for 200h; it can be found that a large number of Sn oxide nanocrystals appear in the Sn crystal; Figure (c) is the HRTEM image of the Sn96.5Ag3Cu0.5 TEM sample after irradiation at a dose rate of 1gy(Si) / s for 200h; it can be found that a large number of SnO2 nanocrystals corresponding to the SnO2 lattice structure appear in the Sn crystal.
[0068] It should be noted that in the above embodiments, as long as the technical solutions are not contradictory, they can be arranged and combined, and those skilled in the art can exhaust all possibilities based on the mathematical knowledge of arrangement and combination. Therefore, the present invention will no longer describe the technical solutions after arrangement and combination one by one, but it should be understood that the technical solutions after arrangement and combination have been disclosed by the present invention.
[0069] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A γ-irradiation-induced nanocrystalline oxide layer on the surface of Sn-based solder, characterized in that: The average grain diameter of the oxide nanocrystals on the surface of Sn-based solder is 10-20nm, and the thickness of the oxide layer is 50nm-1μm.
2. A method for preparing Sn-based solder surface nanocrystals by gamma irradiation-induced oxidation, characterized in that: The following steps are involved: Step 1: Surface pretreatment of the solder; Step 2: Electron irradiation of the solder.
3. The method for preparing Sn-based solder surface nanocrystals by gamma irradiation-induced oxidation according to claim 2, characterized in that: In step 1, the surface of the solder is sanded and polished and then dried to remove surface impurities, wherein the sandpaper polishing is 80 mesh, 240 mesh, 800 mesh, 1500 mesh, 2000 mesh and 3000 mesh, respectively, and the polishing is carried out using 0.5 μm diamond polishing agent and water polishing, respectively.
4. A method for preparing Sn-based solder surface nanocrystals by gamma irradiation-induced oxidation according to claim 2 or 3, characterized in that: Step 2 includes the following steps: Step 2.1: The Sn-based solder sample is placed in a γ irradiation device; Step 2.2: gamma irradiation treatment of the solder sample; Step 2.3: Obtain a solder having a nanocrystalline oxide layer on the surface.
5. The method for preparing Sn-based solder surface nanocrystals by gamma irradiation-induced oxidation according to claim 4, characterized in that: In step 2.1, fix the solder sample on the platform surface.
6. The method for preparing Sn-based solder surface nanocrystals by gamma irradiation-induced oxidation according to claim 5, characterized in that: In step 2.2, the irradiation dose rate is 0.05gy(Si) / s~0.5gy(Si) / s, the irradiation time is 300h~5000h, and the total irradiation dose is 5.4×10 4 gy~9×10 6 gy.
7. The method for preparing Sn-based solder surface nanocrystals by gamma irradiation-induced oxidation according to claim 6, characterized in that: A method for preparing a nanocrystalline oxide layer on the surface of a Sn-based solder induced by gamma irradiation is applied to the oxidation of the Sn-based solder.
8. The method for preparing Sn-based solder surface nanocrystals by gamma irradiation-induced oxidation according to claim 7, characterized in that: Sn-based solders include Sn a1 Bi b1 and / or Sn a1 Zn b1 Alloy, wherein a1 and a2 correspond to the mass percentage content of atoms of each element, 50%≤a1≤100%, 0%≤b1≤50%.
9. The method for preparing Sn-based solder surface nanocrystals by gamma irradiation-induced oxidation according to claim 6, characterized in that: In step 2.2, the temperature is 40°C to 70°C, and the platform speed is 10 rpm to 60 rpm.
10. The method for preparing Sn-based solder surface nanocrystals by gamma irradiation-induced oxidation according to claim 8, characterized in that: The Sn-based solder is in the form of one or more of flake, filament, sphere, block, powder, column, foil or paste.
Citation Information
Patent Citations
Transition metal sulfide and preparation method thereof
CN115820251A
Manufacture of semiconductor device
JP1999186254A
Semiconductor device manufacturing method
JP2006100809A
Method for forming oxide film on valve action metal material
JP2008045190A
INORGANIC NANORODS AND A METHOD OF FORMING THE SAME, AND A PHOTOELECTRODE AND A PHOTOVOLTAIC DEVICE COMPRISING THE INORGANIC NANORODS
WO2012112120A1